Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Semangat Kerja Karyawan PT. POS Indonesia (Persero) Gresik - Indharwan, Ilham; Adiwaty, Mei Retno (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2021)
Research on the effect of work motivation and discipline on spirit at work of PT. POS Indonesia (Persero) Gresik employee has been carried out. The distribution of questionnaires with saturated sampling method to all employees of PT. Pos Indonesia (Persero) Gresik, totaling 63 employees used to obtain data on the partial and simultaneous effect of motivation and work discipline on spirit at work. The respondent data obtained were tested by reliability testing, validity testing and hypothesis testing using the Partial Least Square (PLS) method. The results obtained indicate that the T-statistic value of the work motivation variable is 3.819 > Z = 1.96 and the T-statistic value of the employee discipline variable is 5.106 > Z = 1.96 which indicates that the motivation and work discipline of employee significant effect on spirit at work.